Reductions in body weight and percent fat mass increase the vitamin D status of obese subjects: A systematic review and metaregression analysis - Pannu, Poonam; Zhao, Yun; Soares, Mario (Elsevier Inc., 2016)
The purpose of this review was to confirm a volumetric dilution of vitamin D in obesity. It was based on the hypothesis that weight loss, particularly fat loss, would increase serum 25-hydroxyvitamin D (25OHD) in the obese. We conducted a systematic review of the literature over the last 21 years and included human trials that reported changes in 25OHD, weight, or body composition after weight loss. Study arms were excluded if vitamin D was supplemented, dietary intake exceeded 800 IU/d, or extreme sun exposure was reported. Eighteen of 23 trials that met our criteria documented an increase in vitamin D status with weight loss. Metaregression analyses indicated a marginally significant effect of weight loss on unadjusted weighted mean difference of 25OHD (β = −0.60 [95% confidence interval CI, −1.24 to +0.04] nmol/L; P = .06) and after adjustment for study quality (Jadad score ≥3) (β = −0.64 [95% CI, −1.28 to +0.01] nmol/L; P = .05). The effect of percent fat mass on weighted mean difference of 25OHD was also marginally significant before (β = −0.91 [95% CI, −1.96 to +0.15] nmol/L; P = .08) and after adjustment of study quality (β = −1.05 [95% CI, −2.18 to +0.08] nmol/L; P = .06). Collectively, these outcomes support a volumetric dilution of vitamin D. The slopes of the respective regression lines, however, indicate a smaller increase in 25OHD than would be expected from a direct mobilization of stores into the circulation. Hence, sequestration of 25OHD and its conversion to inactive metabolites would also play a role. Future studies could relate changes in body fat compartments to the enzymatic regulation of 25OHD in response to weight loss.